Scienziati sociali e biologi conservazionisti. Perché è urgente collaborare - Benciolini, Maria; Belardi, Mauro (Antropologia Pubblica, 2024)
The expansion of large carnivores in Europe and Italy, favored by a complex set of natural and human factors, is a major success for biodiversity conservation. Although these species do not yet enjoy a satisfactory conservation status, the population situation is clearly improving.However, the presence of predators also reopens the conflict with farmers and shepherds. The efforts of communication and dissemination of best practices by environmental organizations have not been sufficient so far to mitigate the conflict and promote situations of coexistence.This article proposes some reflections on the social and cultural aspects related to the return of large carnivores and emphasizes the importance of social sciences, and anthropology in particular, in understanding the complexity of the conflict and in finding sustainable solutions.